CURRENT THERAPY OF REPEAT BREEDING IN CROSS-BRED DIARY COWS WITH DILUTED POVIDONE IODINE (Journal of Veterinary Medicine and Animal Production, 2022)
This study was carried out to examine treatment of repeat breeder (RB) dairy cows with diluted Povidone iodine (2%). Sixty cross-bred dairy cows suffer repeat breeding were used to investigate the efficacy of intra-uterine infusion of diluted Pvidone iodine for treatment of repeat breeding in dairy cows. Uterine swabs were collected from uteri of the candidate cows prior treatment. After bacterial culture the uteri of the selected cows were found mildly infected (subclinical endometritis). They were then divided randomly into three equal groups. Group A (n = 20 cows) was intra-uterine infused with 2% Povidone iodine 6 hours pre-insemination. Group B (n = 20 cows) was infused with the same solution 6 hours post-insemination. Group C (n = 20 cows) was left without treatment to serve as control. The potency and efficacy of diluted Povidone iodine to cure repeat breeding in dairy cows was evaluated by studying three parameters, the days open (DO), rate of service per conception and the calving interval (CI). The results of this study revealed that, the DO, rate of service per conception and CI were significantly (P